1998
DOI: 10.1191/096120398678920334
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine in systemic lupus erythematosus: a double-blind, randomized, placebo-controlled study

Abstract: The objective of this study was to investigate the efficacy and safety of bromocriptine (BRC) as an adjunct to conventional treatment in systemic lupus erythematosus (SLE). A prospective, double-blind, randomized, placebo-controlled study compared BRC at a fixed daily dosage of 2.5 mg with placebo. Patients were followed for 2-17 months (mean 12.5 months). Disease activity was assessed using the SLE Disease Activity Index (SLEDAI), numbers of flares were recorded, and serum prolactin (PRL) levels were obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(56 citation statements)
references
References 20 publications
1
55
0
Order By: Relevance
“…In mouse models of systemic lupus erythematosus (SLE), a multiorgan Ab-dependent autoimmune disease, PRL administration increases autoreactive immune responses (17,18), by breaking B cell tolerance and enhancing titers of autoreactive Abs (18). In human SLE, higher serum levels of PRL correlate with greater disease severity, and treatment of SLE patients with bromocriptine (BCR), a dopamine D2 agonist that inhibits PRL secretion, reduces disease activity (19).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelin-mentioning
confidence: 99%
“…In mouse models of systemic lupus erythematosus (SLE), a multiorgan Ab-dependent autoimmune disease, PRL administration increases autoreactive immune responses (17,18), by breaking B cell tolerance and enhancing titers of autoreactive Abs (18). In human SLE, higher serum levels of PRL correlate with greater disease severity, and treatment of SLE patients with bromocriptine (BCR), a dopamine D2 agonist that inhibits PRL secretion, reduces disease activity (19).…”
Section: Ultiple Sclerosis (Ms) Is An Inflammatory Demyelin-mentioning
confidence: 99%
“…This Ͼ7-fold difference is also markedly higher than the 1-2% prevalence of hyperprolactinemia reported for general populations (69,88) and was statistically significant compared with healthy controls (Mantel-Haenzel odds ratio). Prolactin probably stimulates lupus disease activity (89); serum prolactin and disease activity have been positively associated (71,87,90,91); abnormally high prolactin levels during pregnancy in SLE also correlate with disease activity (58,92); and 2 double-blind, placebocontrolled human studies have shown that suppression of prolactin with bromocriptine reduces SLE disease activity (93,94). Interestingly, bromocriptine not only suppresses prolactin but appears to increase estradiol concentrations (95) through increased aromatization of testosterone (96), implying a complex interaction for these hormones in lupus and its disease activity.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…It has also been demonstrated that both nonstimulated and mitogen-stimulated lymphocytes from patients with lupus secrete more prolactin than do control lymphocytes (9,12). Bromocriptine, a drug that blocks prolactin secretion by the anterior pituitary gland, was suggested to have a beneficial effect in patients with SLE in small clinical trials (3,15). In order to study survival and activation of different populations of autoreactive B cells and the effects of prolactin on B cells, particularly anti-DNA production in SLE, an R4A-␥2b mouse model was established and well characterized (24,28).…”
mentioning
confidence: 99%